Bone marrow transplantation prolongs life span and ameliorates neurologic manifestations in Sandhoff disease mice. - Norflus, F (1998)
The GM2 gangliosidoses are a group of severe, neurodegenerative conditions that include Tay-Sachs disease, Sandhoff disease, and the GM2 activator deficiency. Bone marrow transplantation (BMT) was examined as a potential treatment for these disorders using a Sandhoff disease mouse model. BMT extended the life span of these mice from approximately 4.5 mo to up to 8 mo and slowed their neurologic deterioration. BMT also corrected biochemical deficiencies in somatic tissues as indicated by decreased excretion of urinary oligosaccharides, and lower glycolipid storage and increased levels of beta-hexosaminidase activity in visceral organs. Even with neurologic improvement, neither clear reduction of brain glycolipid storage nor improvement in neuronal pathology could be detected, suggesting a complex pathogenic mechanism. Histological analysis revealed beta-hexosaminidase-positive cells in the central nervous system and visceral organs with a concomitant reduction of colloidal iron-positive macrophages. These results may be important for the design of treatment approaches for the GM2 gangliosidoses.